The rise and evolution of agile software development - Hoda, Rashina; Salleh, Norsaremah; Grundy, John (IEEE, 2018)
Agile software development has dominated the second half of the past 50 years of software engineering. Retrospectives, one of the most common agile practices, enables reflection on past performance, discussion of current progress, and charting forth directions for future improvement. Because of agile's burgeoning popularity as the software development model of choice and a significant research subdomain of software engineering, it demands a retrospective of its own. This article provides a historical overview of agile's main focus areas and a holistic synthesis of its trends, their evolution over the past two decades, agile's current status, and, forecast from these, agile's likely future. This article is part of a theme issue on software engineering's 50th anniversary.